The foursome : a novel - Kline, Christina Baker, 1964- (Mariner Books, 2026)
When Eng and Chang Bunker arrive in Wilkes County in 1839, they're not just a curiosity--they're a sensation. Everyone is eager to learn whether the salacious rumors about them are true. Within months, the twins have opened a general store, bought land, and begun building a plantation. Now, word has it, they're looking for wives--and in a place that thrives on gossip and legacy, their ambitions set the community on edge. Sarah and Adelaide Yates, daughters of a once-prominent local family brought low by scandal, are drawn into their orbit. Bold, beautiful Adelaide sees in the twins' fame a chance to reclaim her future. Sarah, quiet and observant, isn't so sure. When the twins' lives become entangled with theirs, they must navigate loyalty, longing, and identity in a world where everything--including race, class, and gender--is rigidly defined. --